An Event Study on Market Reactions to Merger and Acquisition Announcements in Indonesia’s Energy and Telecommunication Sectors - Syarifatun Khafifah; Liana Mangifera (Jurnal Economic Resource, 2026)
This research investigates market responses to merger and acquisition (M&A) announcements in the energy and telecommunications sectors listed on the Indonesia Stock Exchange, using an event study methodology. Abnormal returns are the primary metric for gauging market reaction, calculated using the market model, with the Jakarta Composite Index as the benchmark. The analysis examines several observation periods, including 30- and 60-day timeframes following the announcement, as well as cumulative reactions throughout the event window and discrepancies before and after the announcement date. The results indicate that M&A announcements lead to notable abnormal returns within 30 days and near the announcement date, suggesting short-term and aggregate market effects. Conversely, no significant abnormal returns are detected over the 60 days, and no substantial differences emerge between the pre- and post-announcement phases, implying swift information absorption by the market. These findings corroborate signaling theory and broadly align with the semi-strong form of the efficient market hypothesis, while also emphasizing varied investor responses across timeframes.